A versatile 2A peptide-based bicistronic protein expressing platform for the industrial cellulase producing fungus, Trichoderma reesei. Issue 1 (December 2017) - Subramanian, Venkataramanan; Schuster, Logan; Moore, Kyle; Taylor, Larry; Baker, John; Wall, Todd; Linger, Jeffrey; Himmel, Michael; Decker, Stephen
Abstract Background The industrial workhorse fungus, Trichoderma reesei, is typically exploited for its ability to produce cellulase enzymes, whereas use of this fungus for over-expression of other proteins (homologous and heterologous) is still very limited. Identifying transformants expressing target protein is a tedious task due to low transformation efficiency, combined with highly variable expression levels between transformants. Routine methods for identification include PCR-based analysis, western blotting, or crude activity screening, all of which are time-consuming techniques. To simplify this screening, we have adapted the 2A peptide system from the foot-and-mouth disease virus (FMDV) toT. reesei to express a readily screenable marker protein that is co-translated with a target protein. The 2A peptide sequence allows multiple independent genes to be transcribed as a single mRNA. Upon translation, the 2A peptide sequence causes a "ribosomal skip" generating two (or more) independent gene products. When the 2A peptide is translated, the "skip" occurs between its twoC -terminal amino acids (glycine and proline), resulting in the addition of extra amino acids on theC terminus of the upstream protein and a single proline addition to theN terminus of the downstream protein. To test this approach, we have cloned two heterologous proteins on either side of a modified 2A peptide, a secreted cellobiohydrolase enzyme (Cel7A fromPenicillium funiculosum ) as our target protein, and an intracellular enhanced green fluorescent protein (eGFP) as our marker protein. Using straightforward monitoring of eGFP expression, we have shown that we can efficiently monitor the expression of the target Cel7A protein. Results Co-expression of Cel7A and eGFP via the FMDV 2A peptide sequence resulted in successful expression of both test proteins inT. reesei . Separation of these two polypeptides via the modified 2A peptide was ~100% efficient. The Cel7A was efficiently secreted, whereas the eGFP remained intracellular. Both proteins were expressed when cloned in either order, i.e., Cel7A-2A-eGFP (C2G) or eGFP-2A-Cel7A (G2C); however, eGFP expression and/or functionality were dependent upon the order of transcription. Specifically, expression of Cel7A was linked to eGFP expression in the C2G orientation, whereas expression of Cel7A could not be reliably correlated to eGFP fluorescence in the G2C construct. Whereas eGFP stability and/or fluorescence were affected by gene order, Cel7A was expressed, secreted, and exhibited the expected functionality in both the G2C and C2G orientations. Conclusions We have successfully demonstrated that two structurally unrelated proteins can be expressed inT. reesei using the FMDV 2A peptide approach; however, the order of the genes can be important. The addition of a single proline to theN terminus of eGFP in the C2G orientation did not appear to affect fluorescence, which correlated well with Cel7A expression. The addition of 21 amino acids to theC terminus of eGFP in the G2C orientation, however, appeared to severely reduce fluorescence and/or stability, which could not be linked with Cel7A expression. The molecular biology tool that we have implemented in this study will provide an efficient strategy to test the expression of heterologous proteins inT. reesei, while also providing a novel platform for developing this fungus as an efficient multi-protein-expressing host using a single polycistronic gene expression cassette. An additional advantage of this system is that the co-expressed proteins can be theoretically produced at equimolar ratios, as (A) they all originate from a single transcript and (B) unlike internal ribosome entry site (IRES)-mediated polycistronic expression, each cistron should be translated equimolarly as there is no ribosomal dissociation or reloading between cistrons.